Design of UWB Antenna With Multi slot for Wireless Communication - V.Prashanth, K; Sai Venkatesh, N; Umamaheswari, B; Mukesh, M; Praneeth, G; Ramya Latha, B; Shameem, Syed (International Journal of Engineering and Technology, 2018)
A Compact dual slot ultra-wide band (UWB) Antenna for WLAN and X-Band applications is proposed. The projected antenna is designed for the planar ultra-wide band (UWB) antenna and ultra-wide band (UWB) with two band dismissals. The proposed antenna overall size is 30x40x1.6. The antenna comprises of Rectangular patch imprinted on the Flame Resistant (FR4) substrate with 50Ω input impedance. FR-4 is a composite material made out of fiberglass fabric woven with an epoxy pitch cover that is fire safe (self-dousing). "FR" implies fire resistant, and means that the material meets the standard. This patch consists of dual slot one for WLAN and one for X-band Satellite Communication System. The antenna intended with return loss (RL) >= 10db and frequency ranges between 3.1 to 10.6 GHz with VSWR<2. The antenna works for the applications of wireless local area network (WLAN) system (5.15 – 5.825 GHz), X-band downlink (7.25 - 7.75). The ultra-wide band frequency range for these wireless systems causes interference. To reduce the interference, band notching is done. The WLAN and X-Band satellite communication system bands are forbidden by inserting slots in the patch. The proposed antenna is having high gain at the pass bands while a sharp drop at the forbidden bands.